2019
DOI: 10.1016/j.redox.2019.101100
|View full text |Cite
|
Sign up to set email alerts
|

Mitoquinone ameliorates pressure overload-induced cardiac fibrosis and left ventricular dysfunction in mice

Abstract: Increasing evidence indicates that mitochondrial-associated redox signaling contributes to the pathophysiology of heart failure (HF). The mitochondrial-targeted antioxidant, mitoquinone (MitoQ), is capable of modifying mitochondrial signaling and has shown beneficial effects on HF-dependent mitochondrial dysfunction. However, the potential therapeutic impact of MitoQ-based mitochondrial therapies for HF in response to pressure overload is reliant upon demonstration of improved cardiac contractile function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 63 publications
4
52
0
Order By: Relevance
“…Mitochondrial ROS is also similarly important for pathogenesis of adverse cardiac remodeling and dysfunction. Studies have shown that mitochondria-targeted antioxidants ameliorated cardiac remodeling and functional defects in animal models of pressure-overload induced hypertrophy and diabetes (Ni et al, 2016;Goh et al, 2019). Nicotine administration for 28 days also significantly reduced activity of SOD2 without affecting its gene expression in this study.…”
Section: Discussionsupporting
confidence: 61%
“…Mitochondrial ROS is also similarly important for pathogenesis of adverse cardiac remodeling and dysfunction. Studies have shown that mitochondria-targeted antioxidants ameliorated cardiac remodeling and functional defects in animal models of pressure-overload induced hypertrophy and diabetes (Ni et al, 2016;Goh et al, 2019). Nicotine administration for 28 days also significantly reduced activity of SOD2 without affecting its gene expression in this study.…”
Section: Discussionsupporting
confidence: 61%
“…The majority of proteins are imported into mitochondria, where they undergo folding and assembly (Smyrnias et al, 2019). Production of reactive-oxygen species in pressureoverload (ROS) (Goh et al, 2019) promotes mitochondrial protein misfolding, dysfunction, and a perpetual cycle of progressively worsening mitochondrial damage (Smyrnias et al, 2019). A major source of ROS production are monoamine oxidases (MAOs), and in particular MAO-A (Kaludercic et al, 2014).…”
Section: Metabolic Dysfunctionmentioning
confidence: 99%
“…keap1 and subsequently translocated to the nucleus, which activates downstream defence genes, such as NAD(P) H: quinone oxidoreductase 1 (NQO-1) and peroxide enzyme 1 (Prdx1) 11,12 . As oxidative stress is a common pathogenesis of metabolic diseases, some pharmacological activators of Nrf2, such as mitoquinone 13,14 , bardoxolone methyl 15 , and sulforaphane 16 , have shown beneficial therapeutic potential. However, off-target side effects also were observed because of the unselective activity of Nrf2 [17][18][19] .…”
mentioning
confidence: 99%